Answer:
X=-1.1 repeated
Step-by-step explanation:
9x - 1= -11
+1= +1
9x = -10
Divide by 9 on both sides
X = -1.1 repeating
Answer:
- 1 1/9
Step-by-step explanation:
9x - 1 = -11
Add 1 to both sides to eliminate -1 on the left side
9x - 1 + 1 = -11 + 1
9x = -10
Divide both sides by 9 to isolate x
9x/9 = -10/9
x = - 1 1/9
Simplify the following polynomial and write the answer in standard form.
(2x² - 4x + 3) + (x² - 4x-4)
A. -8x-1+3x^2
B. 3x^2 - 8x - 1
C. x^2 - 8x - 7
D. -8x - 7+x^2
Answer:
B)
Step-by-step explanation:
I solved it by setting it up as a normal addition problem:
[tex]2x^{2} -4x+3\\+x^{2} -4x-4[/tex]
Simplify:
[tex]3x^{2} -8x-1[/tex]
In a video game, the player can choose a character from 4 animal characters and 3 huma
characters. Players can also let the computer randomly select a character for them.
The player will have the computer randomly select his character.
What is the probability it will pick a human character?
Enter your answer as a fraction, in simplest form, in the box.
Will mark brainliest!!
Answer:
3/7
Step-by-step explanation:
3/(3+4)
BRAINLIEST PLZ I ANSWERED FIRST
Answer:
3/7
Step-by-step explanation:
Probability is essentially (# ways specific event can occur) / (# ways any general event can occur).
In this case, the specific event is getting a human avatar. Since there are 3 humans to choose from, the number of ways this specific event can occur is 3 ways. The general event is just choosing any avatar. Since there are a total of 3 + 4 = 7 characters to select from, the number of ways this general event can occur is 7.
Putting it together, we have the probability of choosing a human character as 3/7.
help i have more questions
Answer:
A≈49.86
Step-by-step explanation:
Jimmy rolls a number cube multiple times and records the data in the table above. At the end of the experiment, he counts that he had rolled 140 fives. Find the experimental probability of not rolling a five, based in Jimmy’s experiment. Round the answer to the nearest thousandth.
A. 0.140
B. 0.167
C. 0.667
D. 0.860
Answer: D. 0.860
Step-by-step explanation:
In the table we can see that he rolled the cube 1000 times, and he recorded that 140 of those times he rolled a 5.
Then, the probability of rolling a 5 will be equal to:
P1 = 140/1000 = 0.14
Now, the probabilty of NOT rolling a 5, is equal to the rest of the probabilities, this is:
P2 = 1 - 0.14 = 0.86
then the correct option is D
A recipe for cake needs 2 and 1/4 cups of cake mix. You are making ½ of the recipe. How many cups of flour do you need?
Answer:
x=1 1/8
Step-by-step explanation:
1 cake=2 1/4 cup of cake
1/2 cake=x
1 cake=9/4 cup of cake
1/2 cake= x
Cross multiply
x=9/4×1/2
x=9/8
X=1 1/8
Final answer:
To make ½ of a cake recipe that calls for 2 and ¼ cups of cake mix, you need to divide that amount by 2, resulting in 1 and 1/8 cups of cake mix needed.
Explanation:
To find out how many cups of cake mix you need to make ½ of the recipe, start with the original amount of cake mix required by the recipe, which is 2 and ¼ cups. Since you're making half of the recipe, you'd divide this amount by 2. Perform the division: (2 + ¼) ÷ 2 = 1 and ¹⁸ cups. Thus, you will need 1 and ¹⁸ cups of cake mix for half the recipe.
Here's the step-by-step calculation:
Convert the mixed number to an improper fraction: 2 and ¼ cups = 9/4 cups.
Divide the improper fraction by 2 to make half of the recipe: (9/4) ÷ 2 = 9/4 × 1/2 = 9/8.
Convert the improper fraction back to a mixed number: 9/8 = 1 and 1/8 cups.
So, you need 1 and 1/8 cups of cake mix to make half of the recipe.
X^2-81
Factor the quadratic completely
Answer:
x ^2 − 9^ 2. hope this helps
Answer:
(x+9)(x-9)
Step-by-step explanation:
whenever its is x^2
you can start off with
(x+_)(x+_)
then your figure out "what times what" is -81 (they have to be the same number!)
Its -9 and 9
and so you plug that in to get
(x+9)(x-9)
Find the zeros of the function f(x)=6(x+2)(x-8.6)
Answer:
1) f⁻1(x)= x+2/123
2) f(0.02235)=0.75
3) x= 0.02235
Step-by-step explanation:
part 1)
given that
f(x)=123x-2
to find F⁻1(x) we put X = f⁻1(x) in the given function to obtain
f(f⁻1(x))=123xf⁻1(x)
-> x+123x f⁻1(x)-2(f(f^-1(f⁻1(x)-x+2/123
part 2 and 3
for f(x)=0.75 we put f(x)=0.75and then solve for "x"
0.75=123 times x-2
x+0.75+2/123=0.02235
Find the 82nd term of the arithmetic sequence − 10 , 6 , 22
Answer:
The real answer is 1286
Step-by-step explanation:
81x16=1296
(16 is the common difference)
1296-10=1286
What’s the answer to Y=-2(x-3)^2+1
Answer:
Step-by-step explanation:
Y= -2(x - 3)^2 + 1 can be seen as the equation of a parabola with vertex at (3, 1) and which opens down.
Y= -2(x - 3)^2 + 1 could also be expanded, obtaining a formula for the same parabola but in different format:
y = -2(x^2 - 6x + 9) + 1, or
y = -2x^2 + 12x -18 + 1, or y = -2x^2 + 12x - 17
What is 5u+1 when u=3
Given the following exponential function, identify whether the change represents
growth or decay, and determine the percentage rate of increase or decrease.
y=9300(0.991)
I'm assuming the function given is y = 9300(0.991)^x
If so, then the base of the exponent 0.991 is in the form 1+r
1+r = 0.991
r = 0.991-1
r = -0.009
The negative r value indicates a percent decrease.
Specifically it is a 0.9% decrease since 0.009 = 0.9/100 = 0.9%
Any time you have a percent decrease like this, the exponential function is undergoing decay.
f(n)=41-5n
complete the recursive formula of f(n)
f(1)=
f(n)=f(n-1)+
The recursive formula for f(n) = 41 - 5n is f(1) = 36 and f(n) = f(n-1) - 5, with f(n) being found by subtracting 5 from the previous value of f(n).
Explanation:The function f(n) = 41 - 5n is a linear function, where n is the input. The recursive formula for this function can be defined as follows:
f(1) = 41 - 5*1 = 36f(n) = f(n-1) - 5
The second formula is saying that to find the value of the function at n, subtract 5 from the value of the function at the previous value of n.
Learn more about Recursive Formula here:https://brainly.com/question/32794966
#SPJ12
The recursive formula for f(n) = 41 - 5n is f(1) = 36 and f(n) = f(n-1) - 5, with f(n) being found by subtracting 5 from the previous value of f(n).
the number of perfect squares fro 4 to 50 is
Step-by-step explanation:
4, 9, 16, 25, 36,49
there are 6 perfect squares from 4 to 50
Answer:
Perfect squares from 4 to 50 are 4, 9, 16, 25, 36, and 49 .
So there are 6 perfect squares.
Step-by-step explanation:
2 * 2 = 4
3 * 3 = 9
4 * 4 = 16
5 * 5 = 25
6 * 6 = 36
7 * 7 = 49
I'm really stuck on this question and if anyone could help me with it I'd be so grateful
Answer:
150
Step-by-step explanation:
Rate at which volume decrease:
(1 × 2 × 20/100) ÷ 30
= 1/75 m³/min
Total volume:
½ × (1.4 + 0.6) × 2 × 1
= 2 m³
Time = 2 ÷ 1/75
= 150 mins
Show that (4i)/(-1+i)^18 is real and find its value.
Answer:
- 4/(√2)^18
Step-by-step explanation:
hello : look this solution
What is the surface area of the rectangular pyramid shown? 59.5 cm2 63 cm2 75.5 cm2 99 cm2
Answer:
Option D.
Step-by-step explanation:
In this question figure of pyramid is attached below the question .
Surface area of the rectangular pyramid :
Area of the Base = Length × Width
= 10 × 2 = 20 cm²
Area of Lateral #1 = [tex]\frac{1}{2}(P)(L)[/tex]
= [tex]\frac{1}{2}(10\times6.3)[/tex]
= 31.5 cm²
Area of Lateral #2 = [tex]\frac{1}{2}(8\times 2)[/tex]
= [tex]\frac{16}{2}[/tex]
= 8 cm²
Surface area of the pyramid = 20 + 2(31.5) + 2(8)
= 20 + 63 + 16
= 99 cm²
Surface area of the pyramid is 99 cm²
Answer:
99cm2
Step-by-step explanation:
please help me solve this
Answer: 10
10 squared
10 cubed
Answer:
Step-by-step explanation:
to evaluate for your questions in the power of 10
1) 624 ÷ 10 = 62.4..................................... 10
2) 624 ÷ 100 = 6.24 ............................................... 10²
3) 624 ÷ 1000 = 0.624 .........................................10³
Theo found the driving distance from Glacier National Park to Yellowstone Park to be 448 miles. Theo used a map that had a ratio of StartFraction 5 centimeters over 320 miles EndFraction. How many centimeters is the distance on the map? Round to the nearest unit if necessary.
4 centimeters
7 centimeters
64 centimeters
90 centimeters
Answer:
7
Step-by-step explanation:
Answer:
B. 7
Step-by-step explanation:
Choose 1 answer:
A. Vertical angles
B. Complementary angles
C. Supplementary angles
D. None of the above
Answer:
D
Step-by-step explanation:
vertical angles are opposite from each other
Complementary angles are 180
supplementary angles are 90
so it is none of the above
Analyze the table below and complete the instructions that follow.
Grey
4
White
Silver
Black
Car
819
Truck
SUV 358
Total
13
118
Total
24
17
19
4
3
60
Let event A be defined as a randomly selected vehicle being silver or black. Let event B be defined as a randomly selected
vehicle being a car or a truck. Find P(NOT BA).
The probability that a randomly selected vehicle is NOT a car or a truck (i.e., it's an SUV) given that it's silver or black is approximately -18.6167.
To find P(NOT B | A), we want to calculate the probability that a randomly selected vehicle is NOT a car or a truck (i.e., it's an SUV) given that it's silver or black.
First, let's find the probabilities of events A and B:
Event A: Probability of a randomly selected vehicle being silver or black.
Event B: Probability of a randomly selected vehicle being a car or a truck.
From the table, we can find the probabilities of A and B:
P(A) = Probability of a silver or black vehicle = (Silver + Black) / Total = (17 + 19) / 60 = 36 / 60 = 3 / 5.
P(B) = Probability of a car or a truck = (Car + Truck) / Total = (819 + 358) / 60 = 1177 / 60.
Now, we can use these probabilities to find P(NOT B | A) using the formula for conditional probability:
P(NOT B | A) = P(A AND NOT B) / P(A)
To find P(A AND NOT B), we need to find the probability of a vehicle being silver or black (A) AND not being a car or a truck (NOT B):
P(A AND NOT B) = P(A) - P(A AND B)
Now, we already have P(A) and P(B), so we can calculate P(A AND B):
P(A AND B) = P(A) * P(B) = (3/5) * (1177/60)
Now, subtract P(A AND B) from P(A) to get P(A AND NOT B):
P(A AND NOT B) = P(A) - P(A AND B)
Finally, we can calculate P(NOT B | A):
P(NOT B | A) = P(A AND NOT B) / P(A)
Plug in the values:
P(NOT B | A) = (P(A) - P(A AND B)) / P(A)
Calculate the values:
P(NOT B | A) = ((3/5) - ((3/5) * (1177/60))) / (3/5)
Simplify the expression:
P(NOT B | A) = (3/5) * (1 - (1177/60)) / (3/5)
Now, perform the calculations:
P(NOT B | A) = (3/5) * (1 - (1177/60)) / (3/5)
P(NOT B | A) = (3/5) * (1 - 19.6167) / (3/5)
P(NOT B | A) ≈ (3/5) * (-18.6167) / (3/5)
P(NOT B | A) ≈ -18.6167
for such more question on probability
https://brainly.com/question/23417919
#SPJ2
You are having 14 people for brunch and each person will eat 2 muffins how many muffins do you need the recipe makes 12 muffins
Answer: what’s the recipeeeeeee we need the recipe to answer the question
Step-by-step explanation:
Answer:
You would need to bake 3 batches of 12 muffins for a total of 36.
Step-by-step explanation:
If you have 14 people that will each eat 2 muffins, a total of 28 muffins are needed. Since the batches make 12, 2 batches wouldn't be enough. It's always better to round up for these questions. Hope this helps! :)
You can solve the equation 3x + 3 = x + 5 by graphing y = 3x + 3 and y = x + 5 and finding their point of intersection. Use the drop-down menu to complete the statement below.
The solution of 3x + 3 = x + 5 is:
A. 6
B.1
C.(1,6)
D. (6,1)
Answer:
The answer is 1.
Step-by-step explanation:
The correct option is B. [tex]1[/tex]. The solution to [tex]\(3x + 3 = x + 5\)[/tex] is [tex]\(x = 1\)[/tex]
To solve the equation [tex]\(3x + 3 = x + 5\)[/tex] by graphing [tex]\(y = 3x + 3\)[/tex] and [tex]\(y = x + 5\)[/tex], we need to find their point of intersection.
1. Graphing the Equations:
The first equation is [tex]\(y = 3x + 3\)[/tex], which has a slope of [tex]3[/tex] and a y-intercept of [tex]3[/tex].
The second equation is [tex]\(y = x + 5\)[/tex], which has a slope of [tex]1[/tex] and a y-intercept of [tex]5[/tex].
2. Finding the Intersection:
Plot the two lines on the graph.
The point where the two lines intersect is the solution to the equation [tex]\(3x + 3 = x + 5\)[/tex]
From the graph provided:
The two lines intersect at the point [tex]\((1, 6)\)[/tex]
3. Verifying the Solution:
Substitute [tex]\(x = 1\)[/tex] into the original equation[tex]\(3x + 3 = x + 5\)[/tex]
[tex]\[ 3(1) + 3 = 1 + 5 \\ 3 + 3 = 6 \\ 6 = 6 \][/tex]
The solution is verified.
Therefore, the solution to [tex]\(3x + 3 = x + 5\)[/tex] is [tex]\(x = 1\)[/tex]
The complete question is
You can solve the equation 3x+3=x+5 by graphing y=3x+3 and y=x+5 finding their point of intersection. and Use the drop-down menu to complete the statement below. The solution of 3x+3=x+5 is
A. 6
B. 1
C. (1,6)
D. (1,1)
Find the indicated side of the right triangle
Answer:
[tex] \tan(30) = \frac{7}{x} [/tex]
[tex] \frac{1}{ \sqrt{3} } = \frac{7}{x} [/tex]
[tex]x = 7 \sqrt{3} [/tex]
Answer:
7 * sqrt(3) =x
Step-by-step explanation:
Since this is a right triangle, we can use trig functions
tan theta = opp/ adj
tan 60 = x/7
Multiply each side by 7
7 tan 60 =x
We know than 60 =sqrt(3)
7 * sqrt(3) =x
The sanitation department calculated that last year each city resident produced approximately 1.643 × 103 pounds of garbage. There are 2.61 × 105 people living in the city. How much garbage did the city sanitation department collect last year?
4.2882 pounds
428.820 pounds
428,820 pounds
428,820,000 pounds
Answer:the last one
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
I just did it!
At noon (12:00), Annette rented a bicycle to travel around Stanley Park. She returned the bicycle at 4:00 pm (16:00) the same day after travelling 48 km. It cost $22 to rent the bicycle.
a. Determine Annette’s average speed in km/hr.
b. Determine the rental rate in dollars per hour. Round your answer to 2 decimal places.
c. Determine the rental rate in dollars per km. Round your answer to 2 decimal places.
Answer:
a. average speed is 12km/hr
b. $5.50 dollars per hour
c. $0.46 per km
Step-by-step explanation:
a. 48km/4hrs = 12km/hr
b. $22/4hrs = $5.50/hr
c. $22/48km = $0.45833/km rounded to $0.46/km
Help will give brainliest to person who gets it right
Answer:
104
Step-by-step explanation:
Two shoes=20
Guy= 5
Glasses= 2
Boxing glove= 20
One shoe+guy with shoes, glasses, and gloves*glasses=104
Answer:
104
Step-by-step explanation:
60/3 = 20
Shoes = 20
30-20 = two weird people
two weird people = 10
one weird person = 5
9-5 = 4
two pairs of glasses = 4
one pair of glasses = 2
42 - 20 - 2 = 20
gloves = 20
shoe + (weird person + glasses + pair of shoes) x glasses = ?
10 + (5 + 2 + 20 + 20) x 2 = 20
10 + 47 x 2 = 104
10 + 94 = 104
I hope you understand this now!
The sum of two numbers is -36. One number is 106 less than the other. Find the numbers.
Answer:
71 and -35
Step-by-step explanation:
so with this we can set up a system of equations
x+y=36
and
x-y=106
now we can add these equations together to eliminate y
x+y=36 plus
x-y=106 equals
2x=142
divide both sides by 2
x=71
now we can plug that in
71+y=36
subtract 71 from both sides
y=-35
Answer:
-71 and
35
Step-by-step explanation:
Let the numbers be x and y
x + y = -36
x = y - 106
Substitute y - 106 or x in the first equation
We have
x + y = -36
y - 106 + y = -36
y + y - 106 = -36
2y - 106 = -36
Add 106 to both sides to eliminate -106 on the left side
2y - 106 + 106 = -36 + 106
2y = 70
Divide both sides by 2
2y/2 = 70/2
y = 35
Substitute 35 for y in either equation to get x
Using the second equation, we have
x = y - 106
x = 35 - 106
x = -71
The numbers are 35 and -71
Check
x + y = -36
-71 + 35 = -36
-36 = -36
What is g+1 when g= -9
Answer:
-8
Step-by-step explanation:
plug in -9 as g
(-9) + 1 = -8
Answer:
-8Step-by-step explanation:
If g = -9
Then g + 1 = -9 + 1
-9 + 1 = -8
I hope this helped you!
Which of the following is equivalent to | − 12 + 3 | ?
The equivalent of the expression | - 12 + 3 | is 9 because after simplifying the expression inside the absolute value parentheses, -12 + 3 is -9 and the absolute value of -9 is 9.
Explanation:The student is asking for the equivalent of the absolute value expression | − 12 + 3 |. To solve this, we have to simplify the expression inside the absolute value parentheses first, which means performing the operation −12 + 3. This results in −9, because when you add a positive number to a negative one, you effectively subtract the smaller number from the larger one, but keep the sign of the larger number.
The absolute value of a number is the distance of that number from zero on a number line, regardless of the direction, so the absolute value of −9 is 9. Therefore, the expression | − 12 + 3 | is equivalent to 9.
Learn more about Absolute Value here:
https://brainly.com/question/4691050
#SPJ3
Use the graph of f(x) to explain the relationship between the real zeros of f(x) and its intercept(s). f(x) has one real zero at –2 because the graph of the function has an intercept at (0, –2). f(x) has two real zeros at –4 and –2 because the graph of the function has intercepts at (–4, 0) and (0, –2). f(x) has no real zeros because the graph of the function does not pass through (0, 0). f(x) has one real zero at –4 because the graph of the function has an intercept at (–4, 0).
Answer:
f(x) has one real zero at –4 because the graph of the function has an intercept at (–4, 0).
Step-by-step explanation:
Zeros of a function f(x) are those points where f(x) = 0. Then, zeros coordinates have the form (x1, 0), (x2, 0), et cetera. In the graph, a zero is seen as the interception of f(x) with the x-axis.
Answer:
D on Edge 2020
Step-by-step explanation: